City and poetry in Lisboa, by Sophia de Mello Breyner Andresen - Stoll, Daniela Schrickte (2020)
This article proposes an analysis of the poem Lisboa, by Sophia de Mello Breyner Andresen. Starting with an approach aligned with the feminist literary criticism, it is sought to verify if other forms of reading corroborate, add to or contradict this first approximation. In order to do that, we will analyze the sounds, images and ideas proposed by the poem, as well as the different ways in which the poet has been interpreted by other researchers. In comparison to a poem written by Florbela Espanca concerning the city of Évora, more than fifty years earlier, a historical analysis will also be elaborated. In addition, the relationship between illegible cities and illegible poems will be discussed – in the sense of closing in on their own signs or opening to multiple forms of interpretation and reading.